Overcoming the Emotional Challenges of Cancer Patients through Psychosocial Support - Kusumawaty, Ira; Yunike, Yunike; Inastyarikusuma, Tarrinni; Sri Ananingsih, Esti; Podojoyo, Podojoyo; Elfrida, Solha; Monalisa, Monalisa (Yayasan Rumah Ilmu Professor, 2024)
Cancer not only affects the patient's physical condition but also has significant emotional impacts, such as anxiety, depression and stress. Emotional challenges can affect the quality of life and recovery process of cancer patients. This study aims to identify the types of emotional challenges faced by cancer sufferers and explore the effectiveness of psychosocial support in overcoming these challenges. This research method uses a qualitative approach by collecting data through in-depth interviews and questionnaires involving ten cancer patients from various backgrounds. Research results show that cancer sufferers often experience feelings of fear, hopelessness and social isolation. Anxiety about the future, uncertainty about the effectiveness of treatment, and drastic changes in physical and social roles are the main factors causing emotional distress. Psychosocial support, which includes counselling, group therapy, and assistance from mental health professionals, has proven effective in helping patients manage their emotions. This psychosocial intervention can allow patients to express their feelings, get support from fellow patients, and learn effective coping strategies. This research also found that family and community support plays an important role in the emotional recovery process of cancer patients. Active involvement of family members in counselling and therapy sessions can increase the patient's sense of support and reduce the patient's sense of isolation.Additionally, participation in cancer patient support groups helps them feel more understood and emotionally supported. This study concludes that psychosocial support is an important component of comprehensive cancer care. Psychosocial interventions not only help overcome emotional challenges but also contribute to improving the patient's quality of life. Therefore, healthcare programs must include psychosocial support as an integral part of cancer care, ensuring easy and inclusive access for all patients. Supportive health policies and adequate funding are also needed to implement these services effectively and sustainably.